Delineating historical and contemporary agricultural production regions for China. Issue 2 (4th May 2022) - Veeck, Gregory
ABSTRACT: Chinese and western scholars have long drafted maps delineating China's diverse agricultural regions. Historically, these agro-regionalization schemes were based on dominant crops, first-order soil groups, elevation, climatic variables, or some combination of these factors. However, rapid changes in supply chains, production systems and agro-technologies, including crop breeding, have significantly altered agricultural land use in recent years and blurred the boundaries of classical depictions of China's agricultural regions. This article presents some of the most influential maps of this type for the past century, and adds a new map derived from 39 agricultural production variables selected using Principal Components Analysis (PCA) and aggregated using Ward's hierarchical cluster analysis routine to create a final map of contemporary agricultural regions. This quantitatively derived map of agricultural production regions circa 2016 incorporates variables, such as gross production of key crops, rates of change for production, relative changes to sown area of all major crops and increased use of inputs, such as fertilizer and irrigation, and also includes two traditional classification variables: mean elevation of arable land by province and mean slope of farmland by province in recognition of geomorphological variations across the vast nation.